The Role of Physicians' Digital Tools in Pharmacological Management of Type 2 Diabetes Mellitus - Janež, Andrej; Ješe, Rok; Haluzík, Martin; Rizzo, Manfredi (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: The constantly increasing prevalence of type 2 diabetes mellitus (T2DM) and the advent of new treatment options have made management of T2DM patients more demanding. We aimed to (a) estimate the familiarity of general practitioners with novel T2DM treatment options, (b) determine whether a digital tool can aid in their treatment decisions and (c) demonstrate that an evidence-based digital clinical support tool can be made using an existing digital platform. Materials and methods: This proof-of-concept study consisted of two parts: We first conducted a simple online survey among general practitioners of three European countries to estimate their familiarity with novel T2DM treatment options and to determine whether they believe that a digital tool can aid in their T2DM treatment decisions. We then proceeded to develop a new digital tool that provides quick, evidence-based support for treatment of patients with T2DM using an existing digital platform. Results: The online survey was completed by 129/5278 physicians (94 from Italy, 22 from Czech Republic and 13 from Slovenia). Only 30.7% of all general practitioners reported to be either very or extremely familiar with novel T2DM treatments; the vast majority of participating general practitioners (82.8%) reported that they would find a digital clinical decision support tool for treating T2DM patients either very or extremely useful. A digital tool which features the characteristics deemed most important by the polled physicians was subsequently developed. Conclusions: The results of the online survey showed that familiarity of general practitioners with novel T2DM treatment options is relatively low and that there is a need for digital clinical decision support tools intended to facilitate treatment decisions in T2DM patients. We demonstrated that such a tool can easily be developed using an existing digital platform.
Keywords: Diabetes Mellitus, Type 2; SGLT2; Itálie; GLP-1; digital tools; Humans; Česká republika; Italy; Physicians; lidé; diabetes mellitus 2. typu; DPP4; lékaři; personalized treatment; type 2 diabetes; Evropa; Europe; Czech Republic